Hubungan Sibling Rivalry dengan Kompetensi Sosial Remaja - Meira Dwi Kartika; Mawardi Siregar; Dedy Surya (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
This study aims to see how the relationship between sibling rivalry and social competence. The research design used is an associative quantitative approach. The sample in this study consisted of 57 students at SMPN 4 Timang Gajah aged 13-15 years, sampling was carried out by total sampling because the population was considered small or less than 100. Data collection was carried out using the sibling rivalry questionnaire and social competence. validation sibling rivalry 19 valid items and 3 invalid items. social competence 18 valid items and 8 invalid items. The results of the instrument test performed with Cronbach's alpha obtained reliability results of 0.725 for sibling rivalry and 0.721 for social competence. The results showed that the level of adolescent social competence in SMP N 4 Timang Gajah was at a low level, namely 26 people (45.6%), with a value of (31.5 <x ≤ 40.5). The level of sibling rivalry in adolescents at SMP N 4 Timang Gajah is at a high level, namely 24 people (42.1%) with a value of (52.25 <x ≤ 61.75), and there is a significant relationship between sibling rivalry and adolescent social competence. at SMP N 4 Timang Gajah. With sibling rivalry, it has an effect of 39.5%, and 60.5% is determined by other factors outside of research. There is a negative relationship between sibling rivalry and social competence, that is, the higher the sibling rivalry, the lower the social competence, and as well the contrary.